Harmoni dan Toleransi dalam Pelestarian Budaya Lokal Wetu Telu - Rahmawati, Emma; Lestariani, Nurlita (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Wetu Telu is a religious tradition practised by the Sasak people of West Nusa Tenggara (NTB), which combines elements of Islamic teachings with local traditional practices. The term ‘Wetu Telu’ literally means ‘three times,’ referring to the three times of worship that are considered important in their religious practices. This article aims to explore Wetu Telu practices in West Nusa Tenggara (NTB) as a form of harmony and tolerance in a multicultural society. This research is qualitative in nature, using the literature study method and data analysis based on the Miles and Huberman model. Data was collected through analysis of documents, books, articles, and other related sources that discuss Wetu Telu and intercultural interaction in NTB. The uniqueness of this research lies in the emphasis on the synergy between the Wetu Telu tradition and the values of tolerance in a diverse society. The results show that Wetu Telu practices not only function as religious rituals but also as a means to strengthen interfaith and cultural relations. Wetu Telu teaches respect for differences and the importance of harmony, which is the foundation in maintaining social stability in NTB. In conclusion, Wetu Telu practices in NTB reflect values of harmony and tolerance that can serve as a model for other regions in facing multicultural challenges. This research provides new insights into how local traditions can play a role in building an inclusive and peaceful society.